Molecular epidemiology of malaria and detection of anti-malarial drug resistanceassociated markers (Pfcrt, pfmdr-1, pfdhfr and pfdhps) in Hadhramout governorate, Yemen / Omar Abdullah Ali Bamaga - Omar Abdullah , Ali Bamaga (2017)
Malaria, especially Plasmodium falciparum malaria is one of the main causes of mortality and morbidity worldwide. Yemen is an Eastern Mediterranean country where 68% of its population is at risk of malaria. In 2013, it was estimated that there were 150,000 cases recorded in Yemen with 55 malarial deaths, compared to 900,000 cases in 2000. The anti-malarial treatment policy in Yemen was changed from chloroquine (CQ) to artemisinin combination therapy (ACT) in 2005.The present study is the first in Hadhramout, Yemen which aimed to assess the epidemiology of malaria parasites and to determine the frequency of mutant alleles and genotypes associated with antimalarial drug resistance in Plasmodium falciparum isolates. Blood specimens were collected from seven villages in two different districts of the Hadhramout governorate by houseto-house visits from July 2011 to May 2012. A total of 735 individuals aged 1 to 75 years with a median of 16 years and 22 interquartile range participated in the study. A pre-tested questionnaire was used to gather demographic, socioeconomic and environmental data. Plasmodium species were first identified by microscopy examination and subsequently genomic DNA was extracted from dried archive blood spots of P. falciparum isolates and analyzed using nested PCR. Mutation-specific nested polymerase chain reaction (MS-PCR) and restriction fragment length polymorphism (PCR–RFLP) methods were used to investigate the mutations in the Pfmdr1 (codons 86 and 1246) and Pfcrt (codons 76, 271, 326, 356 and 371) genes. DNA was also amplified using nested PCR and subsequently sequenced for Pfdhfr and Pfdhps genes. Sequences were analyzed for mutations in Pfdhfr at codons 51, 59, 108, and 164 and in Pfdhps at codons 436, 437, and 540. Results of the overall prevalence of malaria parasites in Hadhramout governorate, Yemen via microscopy was 18.8% (138 of 735) with Plasmodium falciparum being the predominant species (99.3%; 137 of 138), followed by Plasmodium vivax (0.7%; 1). Nested PCR detected P. falciparum in four samples iv that were previously negative using microscopy. The combination of microscopy and nested PCR detection resulted in three samples being identified as mixed infections of P. falciparum and P. vivax. The infection rate was higher in Al-Raydah-Qusyer district (21.8%) compared to Hajer district (11.8%). Fifty two percent of those positive for Plasmodium were asymptomatic with low parasite density. The adults had a higher infection rate as compared to children. Univariate analysis identified those whose household’s heads are fishermen (OR = 11.3, 95% CI: 3.13–40.5) and farmers (OR = 4.84, 95% CI: 1.73–13.6) as high-risk groups. A higher number of positive rates were observed in people living in houses with uncemented brick walls (OR = 2.1, 95% CI: 1.32–3.30), without access to toilets (OR = 1.6, 95% CI: 1.05–2.32), without a fridge (OR = 1. 6, 95% CI: 1.05–2.30), or without TV (OR = 1. 6, (95% CI: 1.05–2.30). People living in houses with water collection points located less than 200 meters away were also at higher risk of acquiring malaria (OR = 1.6, 95% CI:1.05–2.30). Knowledge about the importance of using insecticide-treated mosquito nets (ITNs) and indoor residual spraying (IRS) for prevention of malaria was 7% and 2%, respectively. The prevalence of Pfcrt mutations at codons 76, 271, 326 and 371 were 50.4%, 58.7%, 54.3% and 44.9%, respectively. All isolates had wild-type Pfcrt 356 allele. The majority of Pfmdr1 86 alleles (83.3%) and all Pfmdr1 1246 (100%) alleles were also wild type. There was no association between Pfcrt mutations and symptomatology, gender and age groups. For Pfdhfr/Pfdhps mutations, each Pfdhfr mutant allele (I51 and N108) in P. falciparum isolate had a frequency of 84%. Pfdhfr R59 mutant allele was detected in one isolate. Pfdhps at codon G437 mutant allele was detected in 44.7% of Plasmodium falciparum malaria isolates. Frequencies of Pfdhfr double mutant genotype (I51C59N108I164) and Pfdhfr/Pfdhps triple mutant genotype (I51C59N108I164-S436G437K540) were 82.8% and 40.6%, respectively. It is important to note that there was one isolate each which harbored Pfdhfr triple mutant genotype (I51, R59, N108, I164) and v Pfdhfr/Pfdhps quadruple mutant genotype (I51R59N108I164-S436G437K540). In conclusion, several environmental, socioeconomic and behavioral issues were discovered to be the contributing factors to the high prevalence of malaria in this southeast Yemen governorate. High frequencies of point mutations in codons 76, 271, 326 and 371 of P. falciparum, suggested a sustained high CQ resistance even after 6 years of shifting to ACTs. High frequencies of Pfdhfr and Pfdhps mutant alleles and genotypes in P. falciparum isolates from Hadhramout, Yemen, highlight the risk of decreasing efficacy of sulfadoxine pyrimethamine antimalarial drugs. Novel strategies adapted to local situations need to be established in order to improve the effectiveness of malaria control. The current study findings necessitate continuous monitoring of the efficacy of malaria treatment.